Multi-modal characterization of kesterite thin-film solar cells: experimental results and numerical interpretation. (13th July 2022) - Saadaldin, Abdellatif; Slyamov, Azat M.; Stuckelberger, Michael E.; Jørgensen, Peter S.; Rein, Christian; Lucas, Mariana Mar; Ramos, Tiago; Rodriguez-Fernandez, Angel; Bernard, Dominique; Andreasen, Jens W.
Abstract : Scanning X-ray microscopy is shown to be powerful for in situ and operando studies of nanostructured devices such as CZTS solar-cells: nanoscale performance is correlated with composition, and observed trends are understood with simulations. Abstract : We report a multi-modal study of the electrical, chemical and structural properties of a kesterite thin-film solar cell by combining the spatially-resolved X-ray beam induced current and fluorescence imaging techniques for the evaluation of a fully functional device on a cross-section. The data allowed the correlation of the chemical composition, defects at interfaces and inhomogeneous deposition of the layers with the local charge-collection efficiency of the device. We support our observations with Monte Carlo simulations of high-energy X-ray interactions with the semiconductor device, and finite-volume modeling of the charge-collection efficiency.